Low-dose Radiation Therapy in the Management of COVID-19 Pneumonia (LOWRAD-Cov19). Final results of a prospective phase I–II trial. (June 2022) - Sanmamed, Noelia; Alcantara, Pino; Gómez, Sara; Bustos, Ana; Cerezo, Elena; Gaztañaga, Miren; Doval, Anxela; Corona, Juan; Rodriguez, Gabriel; Cabello, Noemi; Duffort, Mercedes; Ortuño, Francisco; et al.
Highlights: LD-RT is feasible and well tolerated treatment for patients diagnosed with COVID-19. One week after LD-RT, 42% of the patients experienced a radiological response. Thirty-nine percent of the patients experienced a rapid respiratory improvement (<72 h). One week after LD-RT, 42% of the patients experienced a radiological response. Patients were discharged a median of 11 days after LD-RT. Abstract: Background and purpose: To evaluate the results of low-dose radiation therapy (LD-RT) to lungs in the management of patients with COVID-19 pneumonia. Material and methods: We conducted a prospective phase I–II trial enrolling COVID-19 patients ≥50 years-old, with bilateral lung involvement at imaging study and oxygen requirement (oxygen saturation ≤93% on room air). Patients received 1 Gy to whole lungs in a single fraction. Primary outcome was a radiological response assessed as severity and extension scores at days +3 and +7. Secondary outcomes were toxicity (CTCAE v5.0), days of hospitalization, changes in inflammatory blood parameters (ferritin, lymphocytes, C-reactive protein, d-dimer and LDH) and SatO2 /FiO2 index (SAFI), at day +3 and +7. Descriptive analyses were summarized as means with standard deviation (SD) and/or medians with interquartile ranges (IQR). A Wilcoxon sign rank test for paired data was used to assess the CT scores and Chi Square was used to assess for comparison of categorical variables. Results: Forty-one patients were included. Median age was 71 (IQR 60–84). Eighteen patients (44%) previously received an anti-COVID treatment (tocilizumab, lopinavir/ritonavir, remdesivir) and thirty-two patients (84%) received steroids during LD-RT. The extension score improved significantly ( p = 0.02) on day +7. Mean baseline extension score was 13.7 (SD ± 4.9) with a score of 12.2 (±5.2) at day 3, and 12.4 ± 4.7 at day 7. No differences were found in the severity score. SAFI improved significantly on day +3 and +7 ( p < 0.01). Median SAFI on day 0 was 147 (IQR 118–264), 230 (IQR 120–343) on day +3 and 293 (IQR 121–353) on day +7. Significant decrease was found in C-reactive protein on day +7 ( p = 0.02) and in lymphocytes counts on day +3 and +7 ( p = 0.02). The median number of days in hospital after RT was 11 (range 4–78). With a median follow-up of 60 days after LD-RT, 26 (63%) patients were discharged, 11 (27%) died because of COVID respiratory failure and 4 (10%) died of other causes. Conclusions: LD-RT is a feasible and well-tolerated treatment that could lead to rapid clinical improvement. Large randomized trials would be required to establish the efficacy of LD-RT to treat COVID-19 pneumonia.